Análisis jurídico de los requisitos para la rescisión de los contratos establecida en el Art. 2370 del Código Civil ante los derechos del acreedor. - Baño Estrella Nayeli Anavel (2024)
The Paulian action, also known as revocation action or rescission action, is a legal mechanism that allows a creditor to challenge legal acts carried out by his debtor that affect his right to collection, by fraudulently or deliberately reducing the debtor's assets. It is a subjective action because it is aimed at protecting the creditor against third parties who have participated in or benefited from acts that have reduced the creditor's financial guarantees. This action allows the creditor to request the rescission of the acts and contracts carried out by the debtor with the intention of defrauding him, in such a way that the assets that were the subject of said act or contract become part of the debtor's assets and can, therefore, , be subject to seizure or execution to satisfy the debt. However, the substantive civil law does not specify when the action to rescind contracts can be carried out or if it is necessary to have a judge's decision in a prior collection process, which creates uncertainty when the creditor attempts to carry out this action to protect the debtor's assets with which he could fulfill the obligation to pay. Keywords: Paulian action, termination of contracts, intention to defraud.